2009
DOI: 10.1088/0004-637x/702/2/1058
|View full text |Cite
|
Sign up to set email alerts
|

The Dual Origin of Stellar Halos

Abstract: We investigate the formation of the stellar halos of four simulated disk galaxies using high resolution, cosmological SPH + N-Body simulations. These simulations include a self-consistent treatment of all the major physical processes involved in galaxy formation. The simulated galaxies presented here each have a total mass of ∼ 10 12 M ⊙ , but span a range of merger histories. These simulations allow us to study the competing importance of in-situ star formation (stars formed in the primary galaxy) and accreti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

49
419
3
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 328 publications
(476 citation statements)
references
References 53 publications
49
419
3
1
Order By: Relevance
“…This confirms the notion that the Galactic halo was formed and assembled very early on as suggested by both theory (Robertson et al 2005;Font et al 2006;Zolotov et al 2009Zolotov et al , 2010Font et al 2011) and observations (e.g. Schuster et al 2012).…”
Section: Implications For the Formation Of The Galactic Halosupporting
confidence: 88%
See 1 more Smart Citation
“…This confirms the notion that the Galactic halo was formed and assembled very early on as suggested by both theory (Robertson et al 2005;Font et al 2006;Zolotov et al 2009Zolotov et al , 2010Font et al 2011) and observations (e.g. Schuster et al 2012).…”
Section: Implications For the Formation Of The Galactic Halosupporting
confidence: 88%
“…Schuster et al (2012) attempted to answer this question by finding that the α-poor stars in their sample are ∼ 2-3 Gyr younger than the α-rich population. This is in favor of the models of Zolotov et al (2009Zolotov et al ( , 2010). Yet, the recent simulations of Font et al (2011) found that in situ stars can be as much as 3-4 Gyr younger than the accreted population.…”
Section: Introductionmentioning
confidence: 95%
“…The latest SPH + N--body simulations of the formation of stellar halos are also finding evidence for a dual origin to the halo. In addition to an outer halo that is dominated by accreted stars from satellite disruption, the inner few tens of kiloparsecs of galaxy halos can contain 50% stars that formed in--situ 26,27 . The local white dwarf population in this study is akin to this latter population, and the derived age measurement of 11.4 +/-- 0.7 billion years agrees very well with the prediction that 70% of the in--situ population in galaxy formation simulations formed by a redshift of 3 (i.e., 11.5 billion years ago) 26 .…”
mentioning
confidence: 99%
“…We investigate when they merged and how they relate to the surviving satellite population. In the past decade several efforts have already focussed on the build-up of Milky Way stellar haloes and/or their chemical evolution, either using hydrodynamical simulations or with semi-analytic techniques (e.g., Salvadori et al 2007;Tumlinson 2006Tumlinson , 2010Zolotov et al 2009;Cooper et al 2010;Font et al 2011;Tissera et al 2013Tissera et al , 2014Cooper et al 2015;Pillepich et al 2014;Lowing et al 2015;Pillepich et al 2015). A specific focus on chemical evolution has been provided by Robertson et al (2005); Font et al (2006a,b), using the hybrid semi-analytic plus N-body approach of .…”
Section: Introductionmentioning
confidence: 99%